PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUKMENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 001 BAGAN KOTA KECAMATAN BANGKO - Antosa, Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Problem on this research was that student’s  achievement on mathematic studies at grade five of SDN 001 Bagan Kota was still low. Student’s who completed 7 student’s (35%) and did not completed 13 studen’ts (65%)  with mean score of  70. This research was done to implement the Cooperative Learning type STAD. It was aimed at improving student’s achievement on Social Studies at the Five Graderes of SDN 001 Bagan Kota by using the STAD type. These results indicate that the first cycle replicates individual student mastery increased from a base score that is 8 people who completed (26.66%) increased by 13 to 20 students (82.95%). In the second cycle increases by 3 people (11.9%) from the first cycle to 39 students (92.85%). In the third cycle increases by 4 people (7.15%) of the cycles of the second cycle to 20 students (100%). In conclusion, the implementation of Cooperative Learning type STAD was able to Improve Student’s achievement on Social Studies at the Five Graderes of  SDN 001 Bagan Kota. Keyword: Cooperatif type STAD, the result of Mathematic